2022
DOI: 10.3389/fneur.2022.919623
|View full text |Cite
|
Sign up to set email alerts
|

Response Predictors of Repetitive Neuromuscular Magnetic Stimulation in the Preventive Treatment of Episodic Migraine

Abstract: BackgroundRepetitive neuromuscular magnetic stimulation (rNMS) of the trapezius muscles showed beneficial effects in preventing episodic migraine. However, clinical characteristics that predict a favorable response to rNMS are unknown. The objective of this analysis is to identify such predictors.MethodsThirty participants with a diagnosis of episodic migraine (mean age: 24.8 ± 4.0 years, 29 females), who were prospectively enrolled in two non-sham-controlled studies evaluating the effects of rNMS were analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Similar findings have also been reported in previous studies investigating rNMS in young adults with episodic migraine (reduction in headache frequency from 7.7 (5.7-12) to 5.3 (1.7-10.3) days/month [median (range)] and 7.7 ± 6.9 to 5.1 ± 4.8 days/month [mean ± SD]; reduction in medication intake from 4 (0-9.7) to 3 (0-9) days/month [median (range)] and 3.3 ± 2.8 to 2.8 ± 1.8 days/month [mean ± SD]) [33,35]. Moreover, a retrospective analysis of the pooled data of both studies showed similar developments, too (reduction in headache frequency from 8.17 ± 4.50 to 6.33 ± 4.38 days/month [mean ± SD], reduction in medication intake from 3.63 ± 2.58 to 3.10 ± 2.44 days/month [mean ± SD]) [50].…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Similar findings have also been reported in previous studies investigating rNMS in young adults with episodic migraine (reduction in headache frequency from 7.7 (5.7-12) to 5.3 (1.7-10.3) days/month [median (range)] and 7.7 ± 6.9 to 5.1 ± 4.8 days/month [mean ± SD]; reduction in medication intake from 4 (0-9.7) to 3 (0-9) days/month [median (range)] and 3.3 ± 2.8 to 2.8 ± 1.8 days/month [mean ± SD]) [33,35]. Moreover, a retrospective analysis of the pooled data of both studies showed similar developments, too (reduction in headache frequency from 8.17 ± 4.50 to 6.33 ± 4.38 days/month [mean ± SD], reduction in medication intake from 3.63 ± 2.58 to 3.10 ± 2.44 days/month [mean ± SD]) [50].…”
Section: Discussionmentioning
confidence: 78%
“…With regard to headache-related disability, a significant reduction in MIDAS scores was reported after rNMS in adults with episodic migraine in previous studies (MIDAS Score reduction from 26.33 ± 13.89 to 15.37 ± 12.30 [mean ± [50]. In congruence, in the current first ever report on the impact of rNMS to the burden of migraine, PedMIDAS scores decreased on average by 14.33 units from baseline to FU, which corresponds to a reduction of 40.9%.…”
Section: Discussionmentioning
confidence: 91%
“…Aside from acupuncture, neuromodulatory therapeutic approaches have been investigated in different forms. While studies have investigated taVNS, RAVANS, and eTNS, many other neuromodulatory bottom-up approaches exist for migraine treatment (e.g., exploiting the trigemino-cervical complex by performing peripheral muscular stimulation to alleviate headache symptoms [151,[163][164][165][166][167]), for which fMRI investigations currently appear to be lacking. Here, fMRI could potentially help to elucidate central mechanisms of action.…”
Section: Discussionmentioning
confidence: 99%
“…A recent open-label study showed preliminary evidence supporting its use in chronic migraine [ 222 ]. Finally, repetitive peripheral magnetic stimulation (rPMS) targeting the muscles in the neck and shoulder muscles has shown efficacy in the prevention of episodic migraine, particularly in patients with a high level of muscular involvement [ 223 , 224 ].…”
Section: Novel Therapies In Migrainementioning
confidence: 99%